2021
DOI: 10.1007/s12026-020-09169-x
|View full text |Cite
|
Sign up to set email alerts
|

A review of COVID-19 convalescent plasma use in COVID-19 with focus on proof of efficacy

Abstract: Convalescent plasma (CP) therapy is rapidly becoming an established consideration in the treatment of COVID-19 patients though there is a need to critically review this area for proof of efficacy. Neutralizing antibodies (NAb) present in CP generated in response to SARS-CoV-2 infection directed against the receptor-binding domain (RBD) of the spike protein are considered to play main role in viral clearance. CP infusion may also help in the modulation of immune response by its immunomodulatory effect. The FDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…Neutralizing antibodies specific to the RBD of SARS-CoV-2 have been discovered in both mice and humans 149,150 , and passive transfer of these antibodies reduces disease severity and offers protection in mouse models of SARS-CoV-2. Convalescent patient serum samples have also yielded promising results in the clinic 151 . However, the natural role that antibodies play during the course of COVID-19 progression remains contested.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…Neutralizing antibodies specific to the RBD of SARS-CoV-2 have been discovered in both mice and humans 149,150 , and passive transfer of these antibodies reduces disease severity and offers protection in mouse models of SARS-CoV-2. Convalescent patient serum samples have also yielded promising results in the clinic 151 . However, the natural role that antibodies play during the course of COVID-19 progression remains contested.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…Similarly, the combination of two recombinant human monoclonal antibodies, casirivimab, and imdevimab, was reported for use in the treatment of COVID-19 [41]. Convalescent plasma (CP), obtained from plasma derived from healthy donors recovered from COVID-19, contains virus-specific antibodies that could provide passive immunity in infected patients [42]. Despite the current standard therapy for COVID-19, new drugs should continue to be investigated as, the long-term effects of drugs and vaccines will be revealed in several years.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the combination of two recombinant human monoclonal antibodies, casirivimab, and imdevimab, was reported for use in the treatment of COVID-19 [ 41 ]. Convalescent plasma (CP), obtained from plasma derived from healthy donors recovered from COVID-19, contains virus-specific antibodies that could provide passive immunity in infected patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including randomized controlled trials (RCTs) as well as observational studies, showed favorable trends in terms of viral load, oxygen demand, progression to intensive care, recovery time, and/or death. (31)(32)(33) Mechanistically, besides the obvious effect of antibodies, the reversals in disease severity could be attributed to a transient reduction in detrimental cytokines and changes in lymphocyte subpopulations. (34) However, plasma therapy could not attain the status of standard care owing to its application based on the clinician's judgment of risk versus benefit to individual patients, lack of sufficient data from RCTs, and uncertainties about its efficacy.…”
Section: Serum/plasma Therapymentioning
confidence: 99%